Association and Dissociation of Grignard Reagents RMgCl and Their Turbo Variant RMgCl⋅LiCl. Issue 23 (6th May 2016) - Schnegelsberg, Christoph; Bachmann, Sebastian; Kolter, Marlene; Auth, Thomas; John, Michael; Stalke, Dietmar; Koszinowski, Konrad
Abstract: Grignard reagents RMgCl and their so‐called turbo variant, the highly reactive RMgCl⋅LiCl, are of exceptional synthetic utility. Nevertheless, it is still not fully understood which species these compounds form in solution and, in particular, in which way LiCl exerts its reactivity‐enhancing effect. A combination of electrospray‐ionization mass spectrometry, electrical conductivity measurements, NMR spectroscopy (including diffusion‐ordered spectroscopy), and quantum chemical calculations is used to analyze solutions of RMgCl (R=Me, Et, Bu, Hex, Oct, Dec, i Pr, t Bu, Ph) in tetrahydrofuran and other ethereal solvents in the absence and presence of stoichiometric amounts of LiCl. In tetrahydrofuran, RMgCl forms mononuclear species, which are converted into trinuclear anions as a result of the concentration increase experienced during the electrospray process. These trinuclear anions are theoretically predicted to adopt open cubic geometries, which remarkably resemble structural motifs previously found in the solid state. The molecular constituents of RMgCl and RMgCl⋅LiCl are interrelated via Schlenk equilibria and fast intermolecular exchange processes. A small portion of the Grignard reagent also forms anionic ate complexes in solution. The abundance of these more electron‐rich and hence supposedly more nucleophilic ate complexes strongly increases upon the addition of LiCl, thus rationalizing its beneficial effect on the reactivity of Grignard reagents. Abstract : Take four ! Four different methods (mass spectrometry, electrical conductivity measurements, NMR spectroscopy, and quantum chemical calculations) are combined to elucidate the speciation of Grignard reagents RMgCl and their so‐called turbo variant RMgCl⋅LiCl in solution. Among the species observed, anionic organomagnesium ate complexes play a key role.